Influence of planting density on the fiber morphology and chemical composition of a new latex-timber clone tree of rubberwood (Hevea brasiliensis Muell.Arg.) - Ahmad Saffian, Harmaen; Md Tahir, Paridah; Harun, Jalaluddin; Jawaid, Mohammad; Hakeem, Khalid Rehman (North Carolina State University, 2014)
In this study, the fiber morphology and chemical constituents of a 4-year-old rubber tree (Hevea brasiliensis Muell. Arg.) from the RRIM 2000 clone series were evaluated. The effects of planting density on the fiber morphology and chemical compositions of the clone of rubber wood were also considered. It is clear that the fibers of the rubber wood samples grown under higher planting density were thicker, with a wider lumen diameter than those grown under lower planting density. There were significant interactions between planting density and the height of the tree from which the samples were taken for all measured fiber properties studied. The chemical composition of the clone of rubber wood was determined as per TAPPI standards. Each of the chemical constituents of the rubber wood displayed statistically significant (at the 95% confidence level) interactions with tree section (low, middle, or high) and planting density. Fiber morphology and chemical composition results showed that juvenile rubber trees could supply fiber to produce particleboard and medium density fiberboard. Compared to mature rubber trees (those more than 25 years old), the studied RRIM 2000 clone rubberwood trees were found to be as compatible for use in the wood industry.